NREM Parasomnias: Retrospective Analysis of Treatment Approaches and Comorbidities - Naina Limbekar; Jonathan Pham; Rohit Budhiraja; Sogol Javaheri; Lawrence J. Epstein; Salma Batool-Anwar; Milena Pavlova (Clocks & Sleep, 2022)
The aim of this retrospective analysis is to determine the most frequently prescribed medications for the treatment of NREM parasomnias and evaluate reported outcomes. We performed a retrospective chart review of all patients with NREM parasomnia diagnosed within Brigham and Women’s Hospital (BWH) clinics examining the date of diagnosis, date of starting therapy, comorbidities, type of medication prescribed, and the reported change in symptoms or side effects at follow-up visits. From 2012 to 2019, 110 patients (59 females, 51 male) at BWH clinics received a diagnosis of NREM parasomnia, including sleepwalking and night terrors. The mean age was 44. Comorbidities included obstructive sleep apnea (OSA) (46%), periodic limb movement syndrome (PLMS) (13%), insomnia (19%), Restless leg syndrome (RLS) (9%), epilepsy (4%), and REM behavior disorder (RBD) (9%). Initial treatment strategies include behavioral and safety counseling only (34%), pharmacological treatment (29%), treatment of any comorbidity (28%), and combined treatment of any of the above (9%). Improvement was reported with: treatment of OSA (n = 23 52% reported improvement), melatonin (n = 8, improvement reported by 88%.,benzodiazepine (n = 7, improvement reported by 57%). Treating comorbid conditions is a frequent treatment strategy, often associated with symptom improvement. The pharmacologic treatment most commonly included melatonin and benzodiazepines. Comprehensive management should include behavioral and safety recommendations, assessment of comorbid conditions, and individually tailored pharmaceutical treatment.